2019
DOI: 10.48550/arxiv.1904.04230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Categorified Chern character and cyclic cohomology

Ilya Shapiro

Abstract: We examine Hopf cyclic cohomology in the same context as the analysis [1,2,3] of the geometry of loop spaces LX in derived algebraic geometry and the resulting close relationship between S 1 -equivariant quasi-coherent sheaves on LX and D X -modules. Furthermore, the Hopf setting serves as a toy case for the categorification of Chern character theory as discussed in [20]. More precisely, this examination naturally leads to a definition of mixed anti-Yetter-Drinfeld contramodules which reduces to that of the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It is furthermore conjectured that the correct coefficients (generalizing the classical ones) are obtained from the true cyclic homology category; this makes exact the analogy between de Rham and Hopf-cyclic coefficients since the former are shown to be so in [1]. More precisely, in [11], a category of mixed anti-Yetter-Drinfeld contramodules is defined by analogy with the derived algebraic geometry case of [1]. This new generalization is conceptual, and furthermore allows the expression of the Hopf-cyclic cohomology of an algebra A with coefficients in M as an Ext (in this category) between ch(A), the Chern character object associated to A, and M itself.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…It is furthermore conjectured that the correct coefficients (generalizing the classical ones) are obtained from the true cyclic homology category; this makes exact the analogy between de Rham and Hopf-cyclic coefficients since the former are shown to be so in [1]. More precisely, in [11], a category of mixed anti-Yetter-Drinfeld contramodules is defined by analogy with the derived algebraic geometry case of [1]. This new generalization is conceptual, and furthermore allows the expression of the Hopf-cyclic cohomology of an algebra A with coefficients in M as an Ext (in this category) between ch(A), the Chern character object associated to A, and M itself.…”
mentioning
confidence: 93%
“…This paper is a descendant of [11] where it is shown that the classic stable anti-Yetter-Drinfeld contramodules are simply objects in the naive cyclic homology category of H M, the monoidal category of modules over the Hopf algebra. It is furthermore conjectured that the correct coefficients (generalizing the classical ones) are obtained from the true cyclic homology category; this makes exact the analogy between de Rham and Hopf-cyclic coefficients since the former are shown to be so in [1].…”
mentioning
confidence: 99%
See 3 more Smart Citations